(untitled) (Global Journal of Medical Research, 2023)
Objective To describe the ultrasonographic profile of nephroblastoma diagnosed at the university clinics of Kinshasa Materials and methods This is a descriptive study it concerns 45 patients with Wilms tumor diagnosed by ultrasonography at the university clinics of Kinshasa from 2016 to 2021 i e an overall period of six years Two ultrasound scanners branded Phillips u-22 and Mindray DC-30 were used